Combination of surgery, radiotherapy and chemotherapy in patients with cervical cancer - Urbański, Krzysztof; Klimek, Małgorzata; Bieda, Tomasz; Piwowarczyk, Sławomir; Urbański, Jacek (Contemporary Oncology/Współczesna Onkologia, 2006)
Introduction: The current state of cervical cancer treatment has been presented. At first surgery and irradiation as independent, radical methods of treatment are presented. Radiotherapy and surgery results in early cervical cancer stage are comparable, and depend on oncology center experience, tradition and resources. Surgical treatment in young women with non advanced cervical cancer allows to preserve ovarian functions. The side effects and degree of sexual dysfunction are similar. In an advanced stage of cervical cancer radiotherapy is the treatment of choice. The coincidence of ovarian tumor, myoma uteri indicates surgery procedure prior to radiotherapy. Combination of surgery and irradiation: Postoperative irradiation eradicates micrometastasis in the lymph nodes left after surgery, parametrial tissues, and surgical margins, decreases locoregional treatment failure, but does not improve distant survival. The role of histopathology examination and ovary translocation in the decision of postoperative irradiation in young women was discussed. The aim and efficacy of combination of surgery and irradiation with concurrent cisplatin based chemotherapy were presented. Radiochemotherapy in cervical cancer: Radiotherapy and concurrent cisplatin based chemotherapy is a new standard in radical and postoperative treatment in patients with unfavorable risk factors. Reliable randomized trials indicate 10 to 18% 3-year survival improvement in patients with early cervical cancer with not involved paraaortal lymph nodes. Radiochemotherapy increases hematological and lower digestive tract side effects and requires concurrent supportive treatment.